Peningkatan Kompetensi Profesional Guru SD Melalui Project Team pada Masa Pandemi Covid 19 - Agus Sriwulan (Universitas Kanjuruhan Malang, 2022)
Teacher skills an absolute requirement in conducting a quality distance education process, especially during the pandemic. Mastery of digital technology is one of strength resource that supports the teacher's pedagogic strategy.This study aims to improve the teachers' professionalism competence of which is focused on technological competence dimensions through a project team. This type of research uses a Classroom Action Research design through four stages of Kemmis-Taggart. The research subjects were 20 teachers of SD Negeri Pandanwangi 1 Malang City. Data collection techniques consisted of observation and questionnaires to determine the implementation of the project team and teachers professional competence of. The results showed an increase in the two aspects studied, including: 1) project team implementation in cycle 1 was 55% and cycle 2 was 86%. Meanwhile 2) the teachers professional competence in cycle 1 was 64% increased to 90% in cycle 2